Path-Planning Module for Tricycle Mobile Robot - Tommy Tommy; Christiand Christiand; Frederikus Wenehenubun (Cylinder : Jurnal Ilmiah Teknik Mesin, 2026)
The path planning module is essential for the navigation of autonomous systems. This research aims to develop a path-planning module in Python programming language using the A* algorithm in conjunction with V-REP software which is used to simulate the path-planning outcome. The A* algorithm is used in this research to implement path-planning for a tricycle mobile robot. Both simulated and physical studies were performed to evaluate the module's performance. In the experiments, inputs of velocity and steering angle are given to the mobile robot at every period as obtained from the simulation regression. The discrepancy between the simulated and physical experimental results was attributed to the inertia force acting on the robot and other factors. The steering angle dominance on a mobile robot also affects the final position of the robot.